Hydrogen bonding between hydroxylic donors and MLCT-excited Ru(bpy)2(bpz)2+ complex: implications for photoinduced electron–proton transfer. Issue 42 (1st May 2019) - Lymar, Sergei V.; Manbeck, Gerald F.; Polyansky, Dmitry E.
Abstract : Rates of electron–proton transfer within the H-bonded exciplexes are evaluated using the free energy correlation with donor's H-bonding acidity. Abstract : The equilibrium constants of the hydrogen bonding (HB) between hydroxylic donors, ROH, and an MLCT-excited Ru(bpy)2 (bpz) 2+ complex, 1 (T), correlated with ROH empirical HB acidities, which could be used for evaluating the unimolecular rate constants of concerted electron–proton transfer within the H-bonded phenol–1 (T) exciplexes.